Two new species of Acmaeodera Eschscholtz, 1829 from the Arabian Peninsula and Mauritania (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini) - Volkovitsh, Mark G. (Zootaxa, 2019)
Acmaeodera (Acmaeodera) strumiai sp. nov. from Oman, Saudi Arabia, Yemen and Mauritania, and A. (Acmaeotethya) dhofarica sp. nov. from Oman and Yemen are described, illustrated and compared with related species.